2021
DOI: 10.1093/rpd/ncab012
|View full text |Cite
|
Sign up to set email alerts
|

Annual Exposure of the Swiss Population From Medical Imaging in 2018

Abstract: Nationwide surveys on radiation dose to the population from medical imaging are recommended in order to follow trends in population exposure. The goal of the 2018 survey was to investigate the current exposure. The invoice coding information was collected in five university hospitals and large clinics. To improve the estimation of the effective dose delivered in computed tomography (CT), we collected dose data from different Dose Archiving Communication Systems. On average, we found that 1.2 radiological exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Some surveys abroad showed similar trend. Two surveys conducted in 2013 and 2018in Swiss showed that the CT scanning frequency increased by about 13% from 117 per 1000 population to 132 per 1000 over the ve years [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some surveys abroad showed similar trend. Two surveys conducted in 2013 and 2018in Swiss showed that the CT scanning frequency increased by about 13% from 117 per 1000 population to 132 per 1000 over the ve years [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…CT is widely used worldwide (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). In 2017, over 84 million CT scans, after accounting for multiple scans, were performed in the United States (29).…”
Section: Ct Use and Low-dose Radiationmentioning
confidence: 99%
“…as numerous individuals undergo radiographic examinations each year (12,(39)(40)(41)(42)(43), raising awareness concerning the risk of X-ray irradiation is particularly important (39). However, to date, at least to the best of our knowledge, no specific literature has addressed methods with which to reduce X-ray exposure in China.…”
Section: Introductionmentioning
confidence: 99%